STUDENTS’ PERCEPTIONS ON THE USE OF PROJECT-BASED DRAMA LEARNING FOR ENGLISH READING - Fiftinova, Fiftinova; Inderawati, Rita; Rosmalina, Ida (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2018)
Abstract: Project-Based Learning provides students opportunities in engaging in a natural-driven context where they use language for talking about their activities. Similarly, Project-based Drama Learning offers beneficial doings which activate students? motivation, independence, potential, critical thinking and language use. This study aims to describe students? perception  on the use of Project-Based Drama Learning  in English language learning. The participants were 30 students who were enrolled in Literature in ELT (English Language Teaching) subject. A questionnaire was given to the students after the project completion.      The data from questionnaire were then analyzed by having theme analysis. The result shows that most of the students gave agreement to the use of Project-Based Drama Learning. The participants believe that it could facilitate English learning. Additionally, the phases which exceedingly facilitate reading capability are Critical Reading and Character Analysis.Keywords: project-based learning, project-based drama learning, literature, Reading, Speaking